2021
DOI: 10.51821/84.1.943
|View full text |Cite
|
Sign up to set email alerts
|

Platelet safety range before splenectomy for hypersplenism : based on 244 cases of splenectomy in hepatolenticular degeneration patients

Abstract: Background and study aims : To investigate the safety and efficacy of splenectomy for hepatolenticular degeneration (HLD) patients with PLT less than 20 × 109/L. Patients and methods : A total of 244 HLD patients with hyper-splenism underwent splenectomy. According to the preopera-tive PLT values, the patients were divided into three groups : group A of 53 patients with PLT < 20 × 109/L ; group B of 92 patients with 20 × 109/L ≤ PLT ≤ 30 × 109/L ; group C of 99 patients with PLT > 30 × 109/L. General in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the beginning, we performed splenectomy in the pursuit to relieve hypersplenism, normalize blood cells level, and meet the requirement of lifelong anti-copper treatment. We have previously reported our experience and results in this regard (23)(24)(25)(26)(27)(28). The expanded sample size of HLD patients involved in this work further confirmed that splenectomy can achieve the desired anti-copper effect and improve the blood cells level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the beginning, we performed splenectomy in the pursuit to relieve hypersplenism, normalize blood cells level, and meet the requirement of lifelong anti-copper treatment. We have previously reported our experience and results in this regard (23)(24)(25)(26)(27)(28). The expanded sample size of HLD patients involved in this work further confirmed that splenectomy can achieve the desired anti-copper effect and improve the blood cells level.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HLD in China is around 6/100,000, and our department is the largest HLD treatment center in China (23)(24)(25)(26)(27)(28). In the beginning, we performed splenectomy in the pursuit to relieve hypersplenism, normalize blood cells level, and meet the requirement of lifelong anti-copper treatment.…”
Section: Discussionmentioning
confidence: 99%